METHODOLOGICAL PROBLEMS IN RUSSIAN PHILOSOPHY OF HISTORY at the end of THE XIX c. – beginning OF THE XX c. - Синяков, С. В.; Сластенко, Е. Ф. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the proportion of subjective and objective in historical cognition. The role ideological aims and conceptual means of research as the most important form of man’s realization of his activity are analyzed.